The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1364/oe.390517
|View full text |Cite
|
Sign up to set email alerts
|

Extruded tellurite antiresonant hollow core fiber for Mid-IR operation

Abstract: We report the first extruded tellurite antiresonant hollow core fibers (HC-ARFs) aimed at the delivery of mid-infrared (Mid-IR) laser radiation. The preform extrusion fabrication process allowed us to obtain preforms with non-touching capillaries in a single step, hence minimizing thermal cycles. The fibers were fabricated from in-house synthetized tellurite glass (containing Zn, Ba and K oxides) and co-drawn with a fluorinated ethylene propylene (FEP) polymer outer layer to improve their mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…ARHCFs are fabricated with the aid of the commonly used stack-and-draw technique [30]. In majority, these fibers are drawn down from high purity fused silica glass (e.g., Suprasil F300) [8], however, due to the high material absorption of this material at the wavelengths above 5 µm, several successful attempts have been reported on fabricating ARHCFs from borosilicate and telluride glass allowing these fibers to efficiently guide light beyond the aforementioned wavelength range [28,31]. Thanks to the unique structure and light guidance properties, ARHCFs deliver better performance and versatility in comparison to other types of HCFs, especially in the area of fiber-aided gas sensing.…”
Section: Light Guidance In Antiresonant Hollow-core Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…ARHCFs are fabricated with the aid of the commonly used stack-and-draw technique [30]. In majority, these fibers are drawn down from high purity fused silica glass (e.g., Suprasil F300) [8], however, due to the high material absorption of this material at the wavelengths above 5 µm, several successful attempts have been reported on fabricating ARHCFs from borosilicate and telluride glass allowing these fibers to efficiently guide light beyond the aforementioned wavelength range [28,31]. Thanks to the unique structure and light guidance properties, ARHCFs deliver better performance and versatility in comparison to other types of HCFs, especially in the area of fiber-aided gas sensing.…”
Section: Light Guidance In Antiresonant Hollow-core Fibersmentioning
confidence: 99%
“…Nevertheless, due to its unique structure, the fiber was characterized by an exceptional immunity to bending, which indicates the excellent robustness, compactness, and versatility of the ARHCF-based absorption cells delivering a few meters long interaction path. The operational wavelength range of the ARHCF-based gas sensors was significantly increased with the development of borosilicate-glass-and telluride-glass-based fibers [28,31], which broke the barrier of 5 µm wavelength range, where the attenuation of silica glass increases rapidly [3,42]. Thanks to this unique feature, the ARHCF technology could be implemented in NO detectors.…”
Section: Wavelength Modulation Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, tellurite hollow core fibers have been developed by an extrusion and draw approach. In 22 the fiber losses of 4.8 and 6.4 dB/m were measured at 5.6 and 5.8 µm, respectively. According to the authors 22 , this gives hope that in the near future it will be possible to fabricate tellurite hollow core optical fibers with sub 1–2 dB/m loss anywhere in the technologically important spectral region between 4.5 and 6.5 µm.…”
mentioning
confidence: 99%
“…In 22 the fiber losses of 4.8 and 6.4 dB/m were measured at 5.6 and 5.8 µm, respectively. According to the authors 22 , this gives hope that in the near future it will be possible to fabricate tellurite hollow core optical fibers with sub 1–2 dB/m loss anywhere in the technologically important spectral region between 4.5 and 6.5 µm. In 23 the authors reported the fabrication of a hollow core fiber drawn from chalcogenide glass 3D printed preform.…”
mentioning
confidence: 99%